MIRERC084/2025: Exploring Civic Engagement Cycle in Kenya: A Behavioral System Mapping Approach: Community communication and pro social behavior in Kenya. - Brenda Ogutu; Jaesica Chandan; Cynthia Mbabazi; Ebby Echoka; Mutwiri, Antony (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
EXECUTIVE SUMMARY Civic engagement is vital for inclusive governance in Kenya, encompassing activities such as community meetings, advocating for change, and holding leaders accountable. It is shaped by factors such as access to information, civil society organizations (CSOs), and social norms. Despite efforts from CSOs, sustained participation often decreases outside of disasters, hampered by misinformation and a lack of reliable information. Informal norms influence behaviors like helping neighbors and sharing information. This study uses Behavioral Systems Mapping to explore these dynamics and identify opportunities to enhance civic engagement in Kenya’s governance. This study aims to generate a deeper understanding of how citizens in Kenya engage with governance processes across the civic engagement cycle, awareness , action , and response, and to identify the behavioral, social, and institutional factors that shape this engagement. The research applies behavioral science frameworks to map the ecosystem of actors, opportunities, and barriers, with the goal of producing actionable recommendations for strengthening prosocial participation. This proposal outlines the methodology for understanding how this engagement cycle exploration will support the behavioral systems mapping process approach. The report defines the scope of the analysis, identifies key stakeholders and target groups, and details the data collection tools, frameworks, and team composition for the assessment. Additionally, it presents timelines for field activities, data analysis, and reporting, ensuring a comprehensive and timely understanding of gender and age dynamics within the systems.